Behavioral and biomedical factors associated with lifestyle modification practices among diagnosed hypertensive patients in pastoral health facilities of southern Ethiopia - Yakob, Tagese; Yakob, Begidu; Jaldo, Mesfin Menza; Dawit, Desalegn; Elias, Chernet; Israel, Eskinder; Abraham, Awoke (Frontiers in Cardiovascular Medicine, 2024)
BackgroundMore than 23 million deaths and 36.5% of disability-adjusted life-years are the result of the direct effects of unhealthy behavior alone. Daily behaviors have strong implications for health outcomes and quality of life. The aim of this study is to determine the behavioral and biomedical factors associated with lifestyle modification practices among diagnosed hypertensive patients in pastoral health facilities of southern Ethiopia.MethodsA facility-based cross-sectional study was conducted among 453 diagnosed hypertensive adult patients in pastoral health of southern Ethiopia from June 1/2023 to July 30/2023. The study population was randomly selected from among patients diagnosed with hypertension that was followed up during the study period using a systematic random sampling technique. The data were entered into Epi-Data-4.6.0.2 and exported to SATAT version 14 for analysis. A binary logistic regression model was fitted to determine independent predictors of lifestyle modification practices among hypertensive patients. An adjusted odds ratio with a 95% confidence interval was used to declare a state of significance.ResultsOut of 453 potential participants approached, 433 agreed to successfully participate in the study, for a response rate of 95.6%. Of the total participants, 56.1% (95% CI, 51.38–60.74) of the patients practiced the recommended lifestyle modifications. Alcohol consumption (AOR = 0.64, 95% CI: 0.42–0.96), ever-practiced reducing salt intake (AOR = 2.48, 95% CI: 1.57–3.93), and low-density lipoprotein cholesterol levels in the blood (>160 mg/dl) (AOR = 3.3, 95% CI: 1.72–6.34) were independently associated with lifestyle modifications in patients with hypertension.ConclusionThis study revealed that the prevalence of lifestyle modification practices (LMP) was low among hypertensive patients. Lifestyle modification is not one-stop practical, but continuous proper awareness creation, counseling, and health education and health promotion are needed to scale up healthy behavior in patients with hypertension to create a good lifestyle.